Pengaruh Faktor Kesadaran Halal, Harga, Pelayanan Dan Religiusitas Terhadap Keputusan Pembelian Orichick Di Kota Semarang - Iqbal Esa; Fuad Mas’ud (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
Indonesia is one of the potential countries in terms of the Muslim consumer market, this is evidenced by the high Muslim population that reaches 209.12 million or around 87% of the total population. The influence of kesadaran halal in society is still considered less than optimal. The culinary business continues to increase, but in fact the halal certification that guarantees the halal haram of a product is still minimal, plus the increasing buying interest of consumers in Semarang City for ready-to-serve products (franchises) which are generally still controlled by foreign parties.This research is a form of quantitative method that is distributed through a questionnaire. The population in this study were Muslim student consumers who had bought and eaten OriChick products in the city of Semarang. The total sample was 100 respondents with a purposive sampling approach. This study uses multiple linear regression analysis techniques where the data is processed using SPSS Statistics 23. The results of the analysis show that the impression of price and ic religiosity has a positive and significant effect on purchasing decisions. Meanwhile, kesadaran halal and service quality variables do not have a significant effect on purchasing decisions. Simultaneously the results of kesadaran halal, price impressions, service quality and ic religiosity have a simultaneous effect on purchasing decisions. The result of the R square value test of 0.346 shows that 34% of purchasing decisions can be explained by independent variables and the remaining 66% is explained by other factors outside the research